Relationship Between Psychological Impacts of COVID-19 and Loneliness in Patients With Dementia: A Cross-Sectional Study From Iran - Mohammadian, Fatemeh; Rezaee, Mahya; Kalantar, Arash; Mohebbi, Niayesh; Motamed, Mahtab (Frontiers in Psychiatry, 2022)
Objectives: Although COVID-19 pandemic has affected people all around the world, the elderly are at a higher risk of suffering from its consequences. One of the serious concerns is developing loneliness and posttraumatic stress symptoms which may contribute to cognitive decline at older ages. This study aimed to examine the psychological responses and loneliness in elderly patients diagnosed with dementia. Methods: Twenty-one patients diagnosed with dementia aged older than 40 and nineteen caregivers were enrolled in the study. Patients undergone a comprehensive neuropsychiatric interview and were assessed with De Jong Gierveld Scale for loneliness and Impact of Event Scale – Revised (IES-R). The severity of dementia was assessed by Functional Assessment Staging Tool (FAST Scale) and The Montreal Cognitive Assessment (MoCA). Results: No significant difference was seen in patients and caregivers in IES-R and loneliness scale. Higher level of avoidance and social and total loneliness were seen in higher FAST levels (p value: 0.046). There was a negative significant correlation between MOCA score and avoidance. Hyperarousal was significantly correlated with emotional loneliness in patients Conclusion: We found a direct relationship between cognitive decline and psychological impacts of COVID-19. Our results highlight the need for more comprehensive studies to further investigate the influence of the pandemic on worsening of cognitive impairment and loneliness in the patients with dementia